Does proactive personality matter? the moderating role of proactive personality in the relationship between vocational maturity and work readiness - Fiki Datul Ismah; Talitha Lintang Pertiwi (Program Studi bimbingan Konseling PPs UNM Makassar, 2026)
Competition in the job market is increasing, requiring vocational high school graduates to possess adequate work readiness. This study aims to examine the effect of vocational maturity on work readiness, with proactive personality as a moderating variable. This quantitative study involved 235 12th-grade vocational high school students in Semarang who were selected using convenience sampling. Data were collected using scales measuring vocational maturity, work readiness, and proactive personality, and analyzed using Moderated Regression Analysis (MRA). The results indicate that vocational maturity has a significant effect on work readiness (R² = 0,343), while the moderating interaction increases the R² value to 0,384 (p < 0,05), representing a 41% increase. The novelty of this study lies in examining the moderating role of proactive personality among vocational high school students. These findings underscore the importance of career guidance services in vocational high schools in fostering students’ proactive personality.